Incorporating digital inking methods in HCI knowledge elicitation - Mohamedally, Dean; Zaphiris, Panayiotis; Petrie, Helen (My University, 2005)
This workshop paper presents digital inking software tools designed to aid and enhance the capabilities of HCI practitioners. The advantages of using these inking tools as part of a HCI practitioners toolkit are firstly to aid in user design and testing with non-technical participants, based on the aesthetic simulacra of digital inking methods as they closely mimic pen-based approaches. Secondly, the digital recognition, storage, processing and retrieval capabilities of such digital ink based data expand and enhance Knowledge Elicitation (KE) models that have been derived from psychology and design methods. The tools presented have been designed through expert Participatory Design (PD) sessions with several HCI practitioners at our research centre. Data is also presented from user-centred studies to illustrate the level of confidence that HCI participants have in using the tools.
Keywords: HCI methods; TabletPC Inking; Mobile Tools for HCI